1936
DOI: 10.1136/bmj.1.3913.11
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anaesthesia

Abstract: TREATMEINT o01 ASTHMA BY t3LThA-IOLET LG{ i reason of the greater wealth of ultraviolet rays in the solar spectrum at those heights. Unfortunately, even this mechainism fails to explain all the clinical phenomena. For example, Case I, during his asthmatic attack, was apparently suffering from acute suprarenal dysfunction which means either that there was an inadequacy of dopasubstance, or else that the suprarenals were failing to convert it to adrenaline. The fact that he did not pigment in an Addisonian manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1939
1939
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…His experiences with spinal anaesthesia formed the basis of an article that was published in the British Medical Journal in 1936. 18 Doyle showed that with proper safeguards spinal anaesthesia was both safe and effective.…”
Section: Surgical Grand Tourmentioning
confidence: 99%
“…His experiences with spinal anaesthesia formed the basis of an article that was published in the British Medical Journal in 1936. 18 Doyle showed that with proper safeguards spinal anaesthesia was both safe and effective.…”
Section: Surgical Grand Tourmentioning
confidence: 99%